(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the efficacy of drain in laparoscopic cholecystectomy. Study Design: Randomized control trial study Place and Duration of Study: This study was conducted at the Department of Surgery, Nishtar Medical University/ Hospital, Multan from January 2018 to December 2018. Materials and Methods: A total 226 patients of both genders undergoing surgical treatment for gall stone disease were included. Patient’s ages were ranging from 20 to 60 years. All the patients were randomly allocated into two groups; Group A (with drain placement) and Group B (without drain placement) and each comprised 113 patients. Sign and symptoms were recorded. Complications were noted post-operatively and on 3 months follow-up. Mortality rate was also examined. Results: There were 70 (61.95%) females and 43 (38.05%) males in group-A while in group-B, 83 (73.45%) were females and 30 (26.55%) were males. All the patients underwent laparoscopic cholecystectomy. Postoperative complications were more in patients who underwent laparoscopic cholecystectomy without drain as compared to those with drain. Conclusion: The rate of complications was higher in patients who underwent cholecystectomy without drain.